A Survey: Children's Rights Post Termination of Parental Rights and Pre‐Adoption. (5th March 2020) - Pelfrey, Theresa M.
Abstract: This survey of the statutory provisions and case law of all 50 states and the District of Columbia includes the rights of children to parental support, inheritance, and familial association remaining upon termination of parental rights. A majority of states terminate all the child's rights at the time parental rights are severed. However, a number of states by explicit statutes or statutory construction have determined that a child's rights to parental support survives termination of parental rights. This survey examines the prevailing law in each state and suggests statutory reforms to protect the legal status and rights of children.